KANDUNGAN FOSFAT DAN NITRAT KAITANNYA DENGAN KEBERADAAN GASTROPODA PADA EKOSISTEM MANGROVE DI PERAIRAN KAMBAPI, KABUPATEN MERAUKE - Sisca Elviana; Nova Suryawati Monika (Faculty of Agriculture Musamus University, 2019)
Mangrove ecosystem is inhabited by a variety of biota, one of the fauna inhabitants of the original mangrove area isgastropods. It is the quality of the waters which certainly has a direct impact on aquatic biota. Nitrate and phosphateare needed by gastropods because they are related to nutrient availability. The purpose of this study is to determinethe phosphate and nitrate contents and analyze the relationship between phosphate and nitrate contents and thepresence of gastropods in the mangrove ecosystem at the Kambapi Beach, Merauke. Data analysis used ecologicaldata of abundance, diversity, dominance and PCA. The results showed that phosphate contents ranged from 0.002-0.04 mg / l and nitrate ranged from 0.007 to 0.19 mg / l, whereas in sediment phosphate contents ranged from 9.63-19.32 mg / l and nitrates ranged from 0.89-4.55mg / l. The results of the analysis of the relationship between thepresence of gastropods and phosphate and nitrate indicates that the parameters of phosphate and nitrate in sedimentsand phosphates in waters have a positive value which means that these parameters affect the presence of gastropoddensity while the environment parameters which correlate negatively is nitrate in the water. This shows that thenitrate contents in water have an inverse relationship with gastropod density.Keywords: Gastropod, Merauke, Phosphate, Nitrate